2018
DOI: 10.5812/semj.65501
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Localized Heat and Cold Therapy on Pain Intensity, Duration of Phases of Labor, and Birth Outcomes Among Primiparous Females: A Randomized, Controlled Trial

Abstract: Background: Pain is a common and unavoidable phenomenon in childbirth, and in terms of severity, childbirth pain is among the most severe pains in human. Objectives: The current study aimed at investigating the effect of localized heat and cold therapy on pain intensity, duration of phases of labor, and birth outcomes among primiparous females. Satisfaction was also compared in the two intervention groups. Methods: The current randomized, controlled trial was conducted on 120 primiparous females in three group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 32 publications
3
17
0
1
Order By: Relevance
“…In the study that used cold application for pregnant women, Shirvani and Ganji 7 reported that the labor duration in the experimental group was shorter. In their study conducted with primipara pregnant women who received cold application to the stomach, lower stomach, and low back, Yazdkhasti et al 25 found no significant differences between the groups in terms of the duration of the first stage of labor, but the duration of the second stage of labor was significantly shorter in the experimental group. 25 This study's findings regarding labor duration are in line with the other prior studies.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the study that used cold application for pregnant women, Shirvani and Ganji 7 reported that the labor duration in the experimental group was shorter. In their study conducted with primipara pregnant women who received cold application to the stomach, lower stomach, and low back, Yazdkhasti et al 25 found no significant differences between the groups in terms of the duration of the first stage of labor, but the duration of the second stage of labor was significantly shorter in the experimental group. 25 This study's findings regarding labor duration are in line with the other prior studies.…”
Section: Discussionmentioning
confidence: 94%
“…In their study conducted with primipara pregnant women who received cold application to the stomach, lower stomach, and low back, Yazdkhasti et al 25 found no significant differences between the groups in terms of the duration of the first stage of labor, but the duration of the second stage of labor was significantly shorter in the experimental group. 25 This study's findings regarding labor duration are in line with the other prior studies. 7,25 When the pregnant women's cervical dilation and effacement values were compared according to the groups, the participants in the experimental group were found to have higher dilation and effacement values.…”
Section: Discussionmentioning
confidence: 94%
“…Given the long-term effects of childbirth experience on women’s physical and mental health and taking into account the Oxford Summit’s emphasis on the prevention of psychological birth trauma (PBT) that negatively affects childbirth experience [ 27 ], studies and interventions aimed to create a positive childbirth experience are considered effective alternatives and solutions [ 10 , 28 ]. In using warm showers, the effect of heat on the sacrum region leads to a reduction in pain intensity as well as the feelings of pleasure and comfort in women, through various mechanisms [ 29 , 30 ]. On the other hand, hydrotherapy reduces the use of drugs and interventions with side effects such as fever [ 31 ], infections caused by bladder catheterization [ 32 ], delivery with spinal anesthesia [ 33 ], and uterine tachysystole [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the results of the study support the hypothesis that perineal pain is experienced less severely in the warm application group than in the control group. In their studies, Fahami et al [13] (2011), Ganji et al [14] (2013), Essa and Ismail [11] (2013), Ahmad and Turky [5] (2010), ­Yazdkhasti et al [18] (2018), Behmanesh et al [19] (2008), and Dahlen et al [20] (2009) reported that warm application to the perineum in the second stage of labor reduces pain levels. When the warmth is applied, the touch and temperature receptors are stimulated and this creates a pleasant feeling.…”
Section: Discussionmentioning
confidence: 99%